Magnet-retained sectional definitive obturator for an infrastructure maxillectomy patient with limited jaw opening: A clinical report - -; Ali Ozdemir; Gulsah Akin; Hakan Akin (Cumhuriyet University, 2011)
A limited oral opening can be a significant problem for patients who must wear removable dental prostheses while inserting or removing prostheses. The treatment of a patient with an infrastructure maxillectomy due to adenoid cystic carcinoma is presented in this clinical report. A sectional obturator prosthesis retained by magnets was fabricated to deal with trismus, fibrosis, and microstomia. The patient's esthetic and functional expectations were satisfied. The new generation of magnets with improved technology provide sufficient denture retention for clinical application. However, further follow-up may be necessary to ascertain the long-term usefulness of the magnet-retained obturator prosthesis, because, not only the deformation of the silicone material may continue to progress but also loss of magnetism can occur because of corrosion.